Let's refresh decaying knowledge: viewing rare complications in practicing confidentiality - Subarimaniam, Neerushah; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Discussions about ethical and legal issues especially confidentiality are becoming more prevalent in the practice of professional counselors. Ethics is defined as code of regulations, refers to restrictions to avoid punishment, and involves effort to become astute counselors. On the other hand, confidentiality involves the practice of keeping and holding all the information shared throughout the client-counselor relationship. Protecting clients’ privacy allows free flow of information between client and counselor. Furthermore, protecting clients’ privacy is not only a matter of moral aspect, it is vital in retaining the bond of trust between counselors and clients. Counselors who fail to uphold clients’ confidentiality will have to face prosecution, clients’ termination of counseling sessions at premature stage, flounder of counselor-client relationship when trust is broken, clients’ mental and emotional instability, and being sued for violating clients’ personal rights. Thus, the primary aim of this article is to address the need to protect clients’ privacy, to discuss issues, and complications in practicing confidentiality in counseling. A total of six articles, although not the latest publications, were randomly selected and studied to enhance understanding about confidentiality and the fundamental of protecting clients’ privacy as a part of good counseling management. Multiple rare complications were reported as obstacles in protecting clients’ privacy: (a) type of focus; (b) working space; (c) corporate ideology; (d) parental consent; and (e) competency level. The counselors are obligated to follow the code of ethics and overcome all the complications by using available counseling guidelines as the benchmark for all the conducts. Furthermore, counselors are expected to help clients to transit from their public persona to a personal one through trustworthy client-counselor relationship. It is increasingly important to raise awareness among counselors and decision makers about ethical and legal issues associated with confidentiality. The complexities of confidentiality issues may warrant interdisciplinary collaborations to improve counseling outcomes.